The Organization, Content, and Case-Finding Effectiveness of HIV Assisted Partner Services in High HIV Morbidity Areas of the United States. (15th April 2022) - Golden, Matthew R.; AugsJoost, Brett; Bender, Melverta; Brady, Kathleen A.; Collins, Lyell S.; Dombrowski, Julia D.; Ealey, Jamila; Garcia, Christopher; George, Dan; Gilliard, Bernard; Harris, Terrainia; Johnson, Cynthia; et al.
Abstract : Background: The contemporary effectiveness of assisted partner notification services (APS) in the United States is uncertain. Setting: State and local jurisdictions in the United States that reported ≥300 new HIV diagnoses in 2018 and were participating in the Ending the Epidemic Initiative. Methods: The study surveyed health departments to collect data on the content and organization of APS and aggregate data on APS outcomes for 2019. Analyses defined contact and case-finding indices (i.e., sex partners named and newly diagnosed per index case receiving APS) and estimated staff case-finding productivity. Results: Sixteen (84%) of 19 jurisdictions responded to the survey, providing APS outcome data for 14 areas (74%). Most health departments routinely integrated APS with linkage of cases and partners to HIV care (88%) and pre-exposure prophylaxis (88%). A total of 19, 164 persons were newly diagnosed with HIV in the 14 areas. Staff initiated APS investigations on 14, 203 cases (74%) and provided APS to 9937 cases (52%). Cases named 6799 partners (contact index = 0.68), of whom 1841 (27%) had previously diagnosed HIV, 2202 (32%) tested HIV negative, 541 (8% of named and 20% of tested partners) were newly diagnosed with HIV, and 2215 (33%) were not known to have tested. Across jurisdictions, the case-finding index was 0.054 (median = 0.05, range 0.015–0.12). Health departments employed 292 full-time equivalent staff to provide APS. These staff identified a median of 2.0 new HIV infections per staff per year. APS accounted for 2.8% of new diagnoses in 2019. Conclusions: HIV case-finding resulting from APS in the United States is low.